2021
DOI: 10.1002/ejic.202100011
|View full text |Cite
|
Sign up to set email alerts
|

Layered Arrangement of 1D Wavy Chains in the Lead‐Free Hybrid Perovskite (PyrCO2H)2BiI5: Structural Investigations and Properties

Abstract: Lead free organic-inorganic hybrid perovskites have attracted increasing attention because of their variety of applications such as photovoltaics or lighting. Here, we reported a new iodobismuthate organic-inorganic perovskite (PyrCO 2 H) 2 BiI 5 where PyrCO 2 H + is the 4-carboxy-1-methylpyridinium. In the room temperature orthorhombic phase, the one-dimensional (1D) inorganic framework which consists of cis-connected corner-sharing BiI 6 octahedra, exhibits a sinusoidal deformation along the chain axis, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It may seem that this is another example of a structure in which the presence of MHy enforces an acentric arrangement of atoms. However, upon comparing the data on structures with the A 2 SbI 5 stoichiometry it can be observed that the majority of them crystallize in non-centrosymmetric or polar space groups [ 26 , 51 , 52 ]. Hence, the absence of a center of symmetry in polymorph I should be attributed to the unique properties of this specific stoichiometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may seem that this is another example of a structure in which the presence of MHy enforces an acentric arrangement of atoms. However, upon comparing the data on structures with the A 2 SbI 5 stoichiometry it can be observed that the majority of them crystallize in non-centrosymmetric or polar space groups [ 26 , 51 , 52 ]. Hence, the absence of a center of symmetry in polymorph I should be attributed to the unique properties of this specific stoichiometry.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrids with the general formula R 2 SbI 5 have already garnered significant attention from scientists as potential functional materials. This is owing to their outstanding properties, which include a strong second harmonic generation (SHG) response [ 32 , 47 , 48 ], ferroelectricity [ 48 , 49 ], a small bandgap with strong absorption ability [ 31 , 33 , 34 , 48 , 49 , 50 , 51 , 52 ], switchable dielectric properties [ 53 ] and excellent thermal stability [ 31 ]. Herein, we show the crystal structure and temperature behavior of two new polymorphic forms, temperature dependent structural phase transitions, thermal characteristics as well as luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…They are assembled by intermolecular interactions between organic cations and inorganic framework anions [6–20] . This combination integrates organic and inorganic parts′ advantages, bringing extraordinary optoelectronic properties, such as dielectric, piezoelectric, ferroelectric, and fluorescent properties [21–37] …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] This combination integrates organic and inorganic parts' advantages, bringing extraordinary optoelectronic properties, such as dielectric, piezoelectric, ferroelectric, and fluorescent properties. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The lead-based phase transition materials have been studied more extensively. For example, it was reported in 2019 that Xiong et al prepared the first organic-inorganic hybrid perovskite (4,4-DFPD) 2 PbI 4 (4,4-DFPD = 4,4-difluoropiperidinium) and revealed interesting ferroelectric vortex structures.…”
Section: Introductionmentioning
confidence: 99%